2016
DOI: 10.1371/journal.pone.0166931
|View full text |Cite|
|
Sign up to set email alerts
|

Do People Eat the Pain Away? The Effects of Acute Physical Pain on Subsequent Consumption of Sweet-Tasting Food

Abstract: Sweet tasting foods have been found to have an analgesic effect. Therefore people might consume more sweet-tasting food when they feel pain. In Study 1, participants were randomly assigned to a pain or non-pain condition and their consumption of cheesecake was measured. Participants ate more cheesecake (a sweet-tasting food) following a painful experience than a non-painful one. In Study 2, participants were randomly assigned to a painful experience or a resource depleting experience (i.e., squeezing a handgri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…Past examination in rodents moreover suggested that High oily eating regimens, rather than strength all things considered, extended desolation behaviors.All the above revelations are suggestive of a connection between BMI types and pain insight among the different blood groups, anyway further investigation is required. Another possible speculation is the incorporation of compound Glycosyltransferases in blend of ABO blood which may add to different nociceptive models as the glycosyltransferases are related with nerve myelination" [36][37][38][39][40][41][42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Past examination in rodents moreover suggested that High oily eating regimens, rather than strength all things considered, extended desolation behaviors.All the above revelations are suggestive of a connection between BMI types and pain insight among the different blood groups, anyway further investigation is required. Another possible speculation is the incorporation of compound Glycosyltransferases in blend of ABO blood which may add to different nociceptive models as the glycosyltransferases are related with nerve myelination" [36][37][38][39][40][41][42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Also, increased activity of the ventral striatum‐medial prefrontal cortex circuitry is associated with higher pain intensity in people with lower back pain 0038. As alterations in the ventral striatum and medial prefrontal cortex circuitry influence eating behaviors by changing the hedonic value of specific foods, people with chronic pain are more likely to overconsume sugary foods than healthy people 0039. Sugar‐containing foods have the ability to increase pain thresholds by activating the endogenous opioid system among animals and human infants 0040.…”
Section: Discussionmentioning
confidence: 99%
“…38 As alterations in the ventral striatum and medial prefrontal cortex circuitry influence eating behaviors by changing the hedonic value of specific foods, people with chronic pain are more likely to overconsume sugary foods than healthy people. 39 Sugar-containing foods have the ability to increase pain thresholds by activating the endogenous opioid system among animals and human infants. 40 For instance, the oral intake of sucrose has an analgesic impact on infants undergoing vaccination.…”
Section: Overweight/obesity and Nutrition In People With Chronic Muscmentioning
confidence: 99%
“…Studies conducted with healthy volunteers have shown that acute physical pain can increase the motivation to attain rewards under laboratory conditions [16, 17]. However, natural reward-related behaviors in patients with chronic pain may be more complicated.…”
Section: Reward-related Behaviors In Patients With Chronic Painmentioning
confidence: 99%